2017
DOI: 10.1126/science.aao5610
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent infection progressively disables host protection against intestinal inflammation

Abstract: Intestinal inflammation is the central pathological feature of colitis and the inflammatory bowel diseases. These syndromes arise from unidentified environmental factors. We found that recurrent non-lethal gastric infections of Gram-negative Salmonella enterica Typhimurium (ST), a major source of human food poisoning, caused inflammation of murine intestinal tissue, predominantly the colon, which persisted following pathogen clearance and irreversibly escalated in severity with repeated infections. ST progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
112
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(122 citation statements)
references
References 69 publications
9
112
1
Order By: Relevance
“…We therefore conclude that LPS detoxification by ALPI in the intestinal lumen is severely impaired in P1 and P2. This conclusion is in keeping with recent work showing how reduced expression of ALPI induced by recurrent non-lethal Salmonella infections impairs intraluminal dephosphorylation/ detoxification of LPS (Yang et al, 2017). Since only two cases of ALPI deficiency were identified, we suggest that this defect is instrumental in predisposing P1 and P2 to severe intestinal inflammation, and our conclusions are strongly supported by data derived from animal models ( 2017).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We therefore conclude that LPS detoxification by ALPI in the intestinal lumen is severely impaired in P1 and P2. This conclusion is in keeping with recent work showing how reduced expression of ALPI induced by recurrent non-lethal Salmonella infections impairs intraluminal dephosphorylation/ detoxification of LPS (Yang et al, 2017). Since only two cases of ALPI deficiency were identified, we suggest that this defect is instrumental in predisposing P1 and P2 to severe intestinal inflammation, and our conclusions are strongly supported by data derived from animal models ( 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Importantly, oral ALPI supplementation protected ALPI‐deficient mice from increased susceptibility to DSS‐induced colitis (Ramasamy et al , ) and from chronic colitis induced by recurrent non‐lethal infections by S. typhimurium (Yang et al , ). This treatment also significantly reduced intestinal inflammation in several mouse models of colitis and prevented LPS translocation (Ramasamy et al , ; Martínez‐Moya et al , ; Rentea et al , ; Heinzerling et al , ; Biesterveld et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…Translational data, primarily generated using animal models, demonstrate an association between enteric infection and GI microbial dysbiosis, with downstream effects on intestinal inflammation 5,27‐37 …”
Section: Resultsmentioning
confidence: 99%
“…Cross‐sectional studies demonstrate unique microbial signatures and T‐cell populations for IBD subtypes 6,7 . GI infection is a common cause of gut dysbiosis, and several studies have reported an association among enteric infection, functionally altered commensal bacteria, and IBD 5,8,9 . By contrast, some microbes, such as Helicobacter pylori and helminths, are inversely associated with IBD, particularly CD.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, statistical methods that jointly model multiple phenotypes have quickly gained popularity in human genetics research [1][2][3] . Leveraging pervasive pleiotropy in the human genome, these methods enhanced the statistical power to identify genetic associations 1,[4][5][6][7] , improved the accuracy of genetic risk prediction 8,9 , revealed novel genetic sharing across diverse phenotypes [10][11][12] , and provided great insights into the genetic basis of a variety of diseases and traits 13,14 .…”
Section: Introductionmentioning
confidence: 99%